The taxonomic value of floral characters in Rapateaceae (Poales-Monocotyledons) - Oriani, Aline [UNESP]; Scatena, Vera Lucia [UNESP] (Springer Nature, 2013)
The floral anatomy of Cephalostemon, Monotrema, Rapatea, Spathanthus, and Stegolepis was studied for taxonomic purposes. All species studied share colleters between the floral parts; sepals, petals, anthers, and style covered by an ornamented cuticle; short epidermal cells with sinuous walls on the abaxial surface of the petals; tetrasporangiate anthers with phenolic idioblasts in the epidermis; endothecium with spiral thickenings; incompletely septate ovary; and anatropous, bitegmic ovules. The floral anatomy is useful not only for characterizing the family, but also for delimiting the subfamilies and genera. Sepals with silica bodies in the epidermal cells; mature anther wall composed of epidermis, endothecium, and middle layer; absence of phenolic idioblasts in the sepals, filaments, and ovary; and stylar epidermal cells with thickened external periclinal wall support Rapateoideae. Cephalostemon and Rapatea show a great number of similarities, corroborating their close relationship indicated in the phylogenetic analyses of the family. Monotrema shares few characters with the genera of Rapateoideae, corroborating its placement in Monotremoideae. Stegolepis shows several distinctive characters, probably related to the greater diversity found in this genus. © 2012 Springer-Verlag Wien.
Keywords: Floral anatomy; Monotremoideae; Rapateoideae; Stegolepis; Cephalostemon; Endothecium; Liliopsida; Monotrema; Poales; Rapatea; Rapateaceae; Spathanthus